(untitled) (Canadian Medical Education Journal, 2024)
Background: Equity-deserving groups are communities marginalized from institutional power by oppressive forces (e.g., racism, sexism, homophobia, ableism). Dear MD to Be is a medical-student-led podcast created to interview physicians of intersectional backgrounds about their institutional experience. This study aims to evaluate the podcast as a tool for knowledge, mentorship, and psychological safety for equity-deserving listeners. Methods: Between February and March 2022, we recruited medical students across all levels of training from English-speaking Canadian medical schools using email listservs and social media. We disseminated a cross-sectional questionnaire assessing demographics, knowledge gained from podcast engagement, attitudes towards podcasts as a tool for mentorship, and psychological/emotional gains from the podcast content. We conducted descriptive and frequency analyses of quantitative data and applied thematic analysis to qualitative data. Results: Thirty-eight individuals completed the entire survey from all levels of training, with 97% self-identifying with at least one equity-deserving group. 100% agreed that the Dear MD to Be podcast was an accessible form of mentorship; participants appreciated self-pacing mentorship and interacting with many narratives. Listeners gleaned lessons about wellness, advocacy work, allyship, cultural imposter syndrome, and navigating discrimination. Furthermore, most listeners felt represented, empowered, and legitimized by podcast content. Conclusions: Podcasts can serve as a medium for accessible equity-centred mentorship. By disseminating multiple underrepresented narratives in medicine, the Dear MD to Be podcast serves as a source of EDI knowledge while contributing to learner safety.